1993
DOI: 10.1002/art.1780360810
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of circulating intercellular adhesion molecule 1 in the sera of patients with rheumatoid arthritis

Abstract: Objective. We sought to assess whether circulating levels of intercellular adhesion molecule 1 (ICAM-1) in patients with rheumatoid arthritis (RA) are elevated and correlate with clinical measures of disease activity and whether this ICAM-1 originates from the synovium.Methods. Circulating ICAM-1 (cICAM-1) levels were determined by sandwich enzyme-linked immunosorbent assay of serum from 61 RA, 18 osteoarthritis (OA), and 11 inflammatory arthritis (IA) patients. In addition, paired serum and synovial fluid sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
2
1

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 15 publications
3
46
2
1
Order By: Relevance
“…A variety of serologic markers have been used to monitor the degree of disease activity in RA, and various new markers have been reported (28)(29)(30)(31). In this study, serum levels of MMP-3 were increased in RA and were correlated with disease activity and also with SF levels of MMP-3, whereas such a correlation was not observed for TIMP-I.…”
Section: Discussionmentioning
confidence: 62%
“…A variety of serologic markers have been used to monitor the degree of disease activity in RA, and various new markers have been reported (28)(29)(30)(31). In this study, serum levels of MMP-3 were increased in RA and were correlated with disease activity and also with SF levels of MMP-3, whereas such a correlation was not observed for TIMP-I.…”
Section: Discussionmentioning
confidence: 62%
“…Unlike their levels in biopsy tissues, serum levels of adhesion molecules can be precisely quantified by enzyme-linked immunosorbent assay (ELISA). Circulating forms of E-selectin, ICAM-1, and VCAM-1 have been described (17), and elevated serum concentrations of ICAM-1 and VCAM-1 have been reported for patients with RA (18)(19)(20). In the case of soluble E-selectin, there have been reports of both unchanged (21) and elevated (22) serum levels in RA.…”
mentioning
confidence: 99%
“…P-selectin (GMP-140, PADGEM protein, orCD62) is a member of the selectin family of adhesion molecules and is a 140 kilodalton membrane protein stored both in the a-granules of platelets and in the Weibel-Palade bodies of endothelial cells (ECs) [1][2][3][4][5][6][7]. Upon the activation of these cells by strong agonists, e.g., thrombin, histamine and in normal human sera and in pathological sera including those of patients with connective tissue diseases and malignan cies [18][19][20][21][22][23]. It was suggested that the measurement of lev els of circulating soluble adhesion molecules is useful as an indicator of inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%